The relationship between motivation, training, and job suitability with employee performance: a study of employees in the private sector - Saudi, Mohd Haizam; Baker, Rogis; Mohd Saudi, Nur Surayya; Mohamed, Rosmah (Karadeniz Technical University, 2021)
Employee performance is an important factor in the success of an organization in the profit-oriented private sector. Deterioration of performance among employees will affect negatively towards the quality and productivity of the organization. The paper aims to examine the relationship between motivation, training, and job suitability for the performance of employees. A total of 136 respondents was involved in this study through distributed to employees working in a private company in northern Peninsular Malaysia. The findings of the study indicate that there is a moderate and significant correlation between motivation, training, and job suitability with employee performance. The findings reveal motivational factors are the most significant contributing factors to employee performance, which motivation is claimed to be crucial in improving employee performance. Employees will be more enthusiastic and strive to perform their duties if they are motivated. In addition, training and job suitability are also important elements in determining the level of performance among employees.